2015
DOI: 10.1002/jmri.25117
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging: Apparent diffusion coefficient histogram analysis for detecting pathologic complete response to chemoradiotherapy in locally advanced rectal cancer

Abstract: Purpose: To investigate the usefulness of apparent diffusion coefficient (ADC) values derived from histogram analysis of the whole rectal cancer as a quantitative parameter to evaluate pathologic complete response (pCR) on preoperative magnetic resonance imaging (MRI). Materials and Methods: We enrolled a total of 86 consecutive patients who had undergone surgery for rectal cancer after neoadjuvant chemoradiotherapy (CRT) at our institution between July 2012 and November 2014. Two radiologists who were blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
1
49
1
Order By: Relevance
“…This was confirmed in another study by Cho et al who reported significantly different 10th and 25th percentile values between responders and non-responders with better diagnostic performance compared to mean ADC [9]. However, similar to the findings of our current study, Choi et al find no benefit in any of the ADC or histogram metrics for pre-treatment prediction of response [10]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was confirmed in another study by Cho et al who reported significantly different 10th and 25th percentile values between responders and non-responders with better diagnostic performance compared to mean ADC [9]. However, similar to the findings of our current study, Choi et al find no benefit in any of the ADC or histogram metrics for pre-treatment prediction of response [10]. …”
Section: Discussionsupporting
confidence: 91%
“…In addition, adding histogram analysis provides information about the distribution of ADC values within the tumor, which can potentially offer valuable additional insights into tumor structure and heterogeneity. This information could be of added benefit to predict response and prognosis, as has been suggested by previous authors [9, 10]. …”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore ADC and histogram features derived from DWI-MRI have shown promise as quantitative imaging biomarkers for therapeutic outcome 4,5,9,10 . Most of these measures are calculated from regions of interest (ROI) of the tumour that are typically obtained after manual tumour segmentation by experienced readers.…”
Section: Introductionmentioning
confidence: 99%
“…Histogram analysis demonstrates tumor heterogeneity and is the foundation for DWI as a biomarker [36][37]. Moreover, these findings suggest that DWI could be a useful tool for personalized care in mesothelioma patients; when a second-line option becomes clinically available (currently a highly unmet need), this type of therapy response evaluation will become especially crucial.…”
Section: Histogram Analysis Of Dw-mri During Early Chemotherapy To Prmentioning
confidence: 97%